High-Temperature Cooperative Spin Crossover Transitions and Single-Crystal Reflection Spectra of [FeIII(qsal)2](CH3OSO3) and Related Compounds - Kazuyuki Takahashi; Kaoru Yamamoto; Takashi Yamamoto; Yasuaki Einaga; Yoshihito Shiota; Kazunari Yoshizawa; Hatsumi Mori (Crystals, 2019)
New Fe(III) compounds from qsal ligand, [Fe(qsal)2](CH3OSO3) (1) and [Fe(qsal)2](CH3SO3)·CH3OH (3), along with known compound, [Fe(qsal)2](CF3SO3) (2), were obtained as large well-shaped crystals (Hqsal = N-(8-quinolyl)salicylaldimine). The compounds 1 and 2 were in the low-spin (LS) state at 300 K and exhibited a cooperative spin crossover (SCO) transition with a thermal hysteresis loop at higher temperatures, whereas 3 was in the high-spin (HS) state below 300 K. The optical conductivity spectra for 1 and 3 were calculated from the single-crystal reflection spectra, which were, to the best of our knowledge, the first optical conductivity spectra of SCO compounds. The absorption bands for the LS and HS [Fe(qsal)2] cations were assigned by time-dependent density functional theory calculations. The crystal structures of 1 and 2 consisted of a common one-dimensional (1D) array of the [Fe(qsal)2] cation, whereas that of 3 had an unusual 1D arrangement by π-stacking interactions which has never been reported. The crystal structures in the high-temperature phases for 1 and 2 indicate that large structural changes were triggered by the motion of counter anions. The comparison of the crystal structures of the known [Fe(qsal)2] compounds suggests the significant role of a large non-spherical counter-anion or solvate molecule for the total lattice energy gain in the crystal of a charged complex.